Can microalgae-bacteria system started with Chlorella vulgaris treat municipal wastewater without mechanical aeration? - Thinojah Thiruchchelvam; Arumugam Sathasivan (Case Studies in Chemical and Environmental Engineering)
Microalgae-bacteria culture could effectively and sustainably treat wastewater and potentially achieve NetZero objectives, especially by eliminating costly mechanical aeration, recovering nutrients, and capturing carbon (energy). Starting with an ideal media for a Chlorella vulgaris, microalgae-bacteria culture was acclimatised to treat solids-removed municipal wastewater (sMW). Hydraulic retention time (HRT) and solids retention time were gradually decreased to 6.67 d and 10 d, respectively. Finally, the external mechanical aeration was stopped. Neither dissolved oxygen (DO) level (remained > saturation DO during daytime) nor the treatment performance (chemical oxygen demand (COD) removal or nitrification) was significantly affected by stopping aeration. COD, inorganic carbon, and total nitrogen reached 50 mg/L, 5 mg/L and 50 mg/L, respectively in the reactor achieving 68 %, 88 % and 29 % removal efficiencies, respectively. The reactor performed like an activated sludge (AS) process in terms of the specific substrate utilisation rate and nitrification, but mixed liquor volatile suspended solids (MLVSS) was low (∼0.1 g/L). There is potential to achieve high organic loading rate and short HRT by increasing MLVSS. Inorganic carbon insufficiency and partial removal of nitrogen and phosphorus indicate the need for further treatment. Overall, this study demonstrates the potential of microalgae-bacteria symbiotic reactor as a viable and sustainable alternative to conventional methods, but future studies are needed to test the limit, risk and opportunities of microalgae-bacteria system in full-scale applications.